Relative weight and length of digestive tract and intestinal histomorphometric measurements of slow-growing broilers of different genotypes - Assis, Saullo Diogo; Leandro, Nadja Susana Mogyca; Arnhold, Emmanuel; Café, Marcos Barcellos; Carvalho, Fabyola Barros de; Stringhni, José Henrique; Santos, Raphael Rodrigues dos (Semina: Ciências Agrárias, 2021)
An experiment was conducted to investigate the development of the digestive system in slow-growing broilers of different strains. The experiment involved a total of 544 one-day-old chicks, 136 of each of four genotypes, namely, Label Rouge Pesadão, Label Rouge Pescoço Pelado, Carijó and Carijó Pescoço Pelado. The birds were distributed in a completely randomized design with four treatments (genotypes) and eight replicates of 17 animals each. Live weight, digestive tract development and intestinal histomorphometric measurements were evaluated at different ages. Significant differences (p < 0.05) were observed between the strains for live weight, relative weight and length of digestive tract organs and intestinal histomorphometric measurements at one, seven and 28 days of age. The Carijó strain showed greater weight and development of digestive organs than the Carijó Pescoço Pelado strain. There was a difference (p < 0.05) for histomorphometric measurements of the small intestine between the strains at the evaluated ages. The Carijó Pescoço Pelado and Label Rouge Pescoço Pelado strains showed higher villi and higher villus:crypt ratios in the duodenum, jejunum and ileum. The slow-growing strains differ in performance regarding the relative weights and lengths of digestive tract organs and intestinal histomorphometric measurements.